1995
DOI: 10.1083/jcb.130.3.701
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of neurite outgrowth in PC12 cells by EGF and KCl depolarization: a Ca(2+)-independent phenomenon.

Abstract: Abstract. MAP kinase activity is necessary for growth factor induction of neurite outgrowth in PC12 cells. Although NGF and EGF both stimulate MAP kinase activity, EGF does not stimulate neurite extension. We report that EGF, in combination with KC1, stimulates neurite outgrowth in PC12 cells. This phenomenon was independent of intracellular Ca 2÷ increases and not due to enhancement of MAP kinase activity over that seen with EGF alone. However, EGF plus KC1 increased intracellular cAMP, and other cAMP elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 63 publications
3
55
0
Order By: Relevance
“…We next wanted to examine the effect of EGF on PKA activity in PC12 cells. Since EGF was shown not to increase cAMP or activate PKA in PC12 cells (14,36), it was unexpected when EGF induced an AKAR4-Kras response of 9.1% Ϯ 1.2% (n ϭ 12) (Fig. 1E, purple diamonds, and F, top).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next wanted to examine the effect of EGF on PKA activity in PC12 cells. Since EGF was shown not to increase cAMP or activate PKA in PC12 cells (14,36), it was unexpected when EGF induced an AKAR4-Kras response of 9.1% Ϯ 1.2% (n ϭ 12) (Fig. 1E, purple diamonds, and F, top).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, activated PKA and Epac converge to activate Rap1 (26), the aforementioned mediator of sustained ERK activity (36,37). In contrast, EGF was not known to increase cAMP or activate PKA in PC12 cells (14). Interestingly, a number of studies have shown that when EGF is used in conjunction with cAMP-elevating agents, neurite outgrowth can be induced in PC12 cells (9,14,15,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PLCc2, but not PLCc1, is required for the activation of CRE-mediated transcription Previous reports have indicated that the activation of cAMP or Ca 2+ signaling pathways induces CRE-mediated transcription in PC12 cells (Sheng et al 1991;Mark et al 1995;Thompson et al 1995;Impey et al 1998). To probe the role of PLCcs in CRE-mediated transcription induced by activation of the cAMP and Ca 2+ signaling pathways, we examined the effects of knockdown of the expression of PLCc1 and c2 in PC12 cells on this process.…”
Section: Siplcc1 and Siplcc2 Reduce Plcc1 Or Plcc2 Expression Respecmentioning
confidence: 99%
“…One important determinant seems to be the duration of the signal. In the neuronal cell line PC12, short duration of MAPK-1,2 signaling is thought to promote proliferation, whereas sustained MAPK-1,2 signaling is thought to promote differentiation [50][51][52]. Recent studies by Murphy and co-workers have elucidated a feed-forward mechanism that decodes the duration of MAPK activation in terms of IEGs expression and function [53,54].…”
Section: Anatomy Of a Time Bridge: Feed-forward Relaysmentioning
confidence: 99%